- This topic has 2 replies, 3 voices, and was last updated 7 years, 7 months ago by .
You must be logged in to reply to this topic.
Viewing 3 posts - 1 through 3 (of 3 total)
You must be logged in to reply to this topic.
You must be logged in to reply to this topic.
11. Solve
x – 3y = 6
4x + 3y = 9
using the substitution method
X-3y=6
4x+3y=9 Plug in y=1 into the original equation.
X-3(-1)=6
X+3=6
-3=-3
X=3
Multiply -4 to the first equation.
-4x+12y=-24
4x+3y=9. Y=1. X=3
__________
15y=-15/15
Y=1
x – 3y = 6
4x + 3y = 9
X= 3y+6
4(3y+6) +3y = 9
12y+24 + 3y = 9
15y + 24 = 9
15y = -15
y= -1
X= 3(-1)+6
X = 3
{3,-1}
You must be logged in to reply to this topic.
Ursula C. Schwerin Library
New York City College of Technology, C.U.N.Y
300 Jay Street, Library Building - 4th Floor
Our goal is to make the OpenLab accessible for all users.